Greening EU competition law and policy - Kingston, Suzanne (Cambridge antitrust and competition law series, 2012)
"One of the fundamental challenges currently facing the EU is that of reconciling its economic and environmental policies. Nevertheless, the role of environmental protection in EU competition law and policy has often been overlooked. Recent years have witnessed a shift in environmental regulation from reliance on command and control to an increased use of market-based environmental policy instruments such as environmental taxes, green subsidies, emissions trading and the encouragement of voluntary corporate green initiatives. By bringing the market into environmental policy, such instruments raise a host of issues that competition law must address. This interdisciplinary treatment of the interaction between these key EU policy areas challenges the view that EU competition policy is a special case, insulated from environmental concerns by the overriding efficiency imperative, and puts forward practical proposals for achieving genuine integration"--